Antithrombotic Effects of Five Organic Extracts of Bangladeshi Plants In Vitro and Mechanisms in In Silico Models. (17th May 2015) - Mahmud, Sakib; Akhter, Samina; Rahman, Md. Atiar; Aklima, Jannatul; Akhter, Shaheen; Merry, Syeeda Rayhana; Jubair, S. M. Rakibul; Dash, Raju; Emran, Talha Bin
Abstract : This research was carried out to investigate the thrombolytic effects of the methanolic extracts of five Bangladeshi plants. Phytochemical metabolites of those plants have been identified to elucidate whether the plant-derived metabolites are linked with the thrombolytic effects. Potential computer aided models were adopted in this study to find out a structure-function correlation between the phytochemical constituents and thrombolytic effects using the secondary metabolites as ligands and tissue plasminogen activator (t-PA) as receptor for the best fit ligand-receptor interaction.